Sistem Informasi Penjualan Barang pada UD Henry Teknik Berbasis Desktop - Amelia Agustina; Mira Ziveria (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
UD Henry is a trading company specializing in hardware and engineering. In conducting its business procedures, UD Henry Teknik continues to use paper. Using a memorandum to record the transaction when just the employee's recollection is used to provide information on the pricing and stock of the goods. This research examines the construction of a desktop-based sales information system at UD Henry Teknik that can aid in business activities like as inventory management, transaction recording, and sales report management. This study employs the prototyping and modeling of the system using a unified modelling language (UML). During the construction of the system, mySQL and Netbeans IDE were utilized. Based on the results of black box testing, the system complies with user requirements and functions appropriately.